Effect of Biofertilizer Formulation Parameter on Changes in Soil and Water Physical Media Peat - Yose Riadi; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from December 2017 to February 2018 in the Kualu Nenas village Tambang Distric Kampar Regency and in Environmental Quality Aquaculture, Faculty of Fisheries and Marine University of Riau. This study aims to determine the effect of biofertilizerin the physicalchanges. The treatments of the result applied were without formulation Biofertilizer (P0), formulation Biofertilizer 75 g/container (P1), formulation Biofertilizer112,5  g/container (P2), formulation Biofertilizer150 g/container (P3) and formulation Biofertilizer187,5 g/container (P4). The results of this study showed formulation of Biofertilizer affected on physical properties specially turbidity and coarse fiber, the best of Biofertilizerof the result is P4 (187,5 g/container ) of turbidity and coarse fiber wen 21,25 NTU and 7,50%. Keywords :Biofertilizer, Physical Parameter, Peat Land